Digital Rectal Examination and Balloon Expulsion Test in the Study of Defecatory Disorders: Are They Suitable as Screening or Excluding Tests? - Ana C. Caetano; André Santa-Cruz; Carla Rolanda (Canadian Journal of Gastroenterology and Hepatology)
Background. Rome III criteria add physiological criteria to symptom-based criteria of chronic constipation (CC) for the diagnosis of defecatory disorders (DD). However, a gold-standard test is still lacking and physiological examination is expensive and time-consuming. Aim. Evaluate the usefulness of two low-cost tests—digital rectal examination (DRE) and balloon expulsion test (BET)—as screening or excluding tests of DD. Methods. We performed a systematic search in PUBMED and MEDLINE. We selected studies where constipated patients were evaluated by DRE or BET. Heterogeneity was assessed and random effect models were used to calculate the sensitivity, specificity, and negative predictive value (NPV) of the DRE and the BET. Results. Thirteen studies evaluating BET and four studies evaluating DRE (2329 patients) were selected. High heterogeneity (I2>80%) among studies was demonstrated. The studies evaluating the BET showed a sensitivity and specificity of 67% and 80%, respectively. Regarding the DRE, a sensitivity of 80% and specificity of 84% were calculated. NPV of 72% for the BET and NPV of 64% for the DRE were estimated. The sensitivity and specificity were similar when we restrict the analysis to studies using Rome criteria to define CC. The BET seems to perform better when a cut-off time of 2 minutes is used and when it is compared with a combination of physiological tests. Considering the DRE, strict criteria seem to improve the sensitivity but not the specificity of the test. Conclusion. Neither of the low-cost tests seems suitable for screening or excluding DD.